Respons pajak daerah: Impresi covid-19? - Ismiyanti, Ismiyanti; Dewata, Evada; Dwitayanti, Yevi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Covid-19 pandemic 2020 caused decrease Regional Tax Revenue in Palembang. The purpose of research to analyze comparison of Regional Tax receipts in Palembang before and during the Covid-19 and to analyze the comparison of Land and Building Tax receipts in 18 Districts in Palembang before and after the adjustment Tax Object Selling Value rate. The type research is descriptive quantitative with secondary data types use panel data with time series and cross section data types analyzed using Paired Sample T Test technique through the SPSS version 26 application. The total population is 120 consisting of 12 types regional taxes 2018-2021 period and Land and Urban Building Tax in 18 sub-districts 2017-2020 period. The sampling technique is saturated sampling so number of samples is 120. The results research are the types regional taxes affected by the Covid-19 are Parking and Hotel Tax. The sub-districts affected adjustment Tax Object Selling Value rate are 9 sub-districts, Sukarami, Ilir Timur I, Kalidoni, Ilir Timur II, Jakabaring, Kemuning, Ilir Timur III, Ilir Barat I, and Alang-Alang Lebar. The implications this research is can be informative suggestions in formulating regulations as a corrective step to increase local tax revenues in the city of Palembang.